Analysis of Online Academic Writing Tools Usage among Postgraduate Students in North-west Nigeria - Yakubu, Muhammad Auwal; Sain, Zohaib Hassan; Lawal, Uthman Shehu; Budiman, Septian Arief; Permana, Dian (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study investigates the usage of online academic writing tools and reference management software among postgraduate students in North-west Nigeria. A descriptive survey design was employed, with a sample of 420 doctoral students from four regional universities. Data was collected using a structured questionnaire and analyzed using descriptive and inferential statistics. The findings reveal that Google Docs and Authorea are the most widely used online tools for academic writing and collaboration, followed by Overleaf and OneNote. Surprisingly, Microsoft Office 365 showed lower adoption rates. Regarding reference management software, Mendeley and Zotero emerged as the clear favourites, with EndNote and Citavi also showing significant usage. Statistical analysis indicated significant differences in the use of online tools for academic writing and collaboration and the types of reference management software used among postgraduate students. These differences could be attributed to individual preferences, institutional recommendations, or varying levels of technological literacy. The study contributes to understanding digital literacy and technology adoption in higher education in developing countries. It provides valuable insights for educational institutions, policymakers, and software developers to support postgraduate students' academic endeavours. Recommendations include implementing digital literacy programs and developing standardized sets of recommended tools to enhance research productivity and collaboration among doctoral students in North-west Nigeria.